Marketing strategies of banks in the consumer loans market - Lee, Bee Lan (2015)
The motivation for this report has arisen from our observation of the recent increase in promotional efforts of banks in pursuing the 'man-on-the street'. Statistics has shown an increasing amount of loans to professionals and private individuals too. It would, therefore, be interesting for aspiring bankers to take an overview of the strategies that the different banks adopt in responding to the changes in the competitive environment. Case study approach was used as the primary research approach. The marketing strategies adopted by three banks, which included two local banks and one foreign bank, were studied. Data was collected through personal interviews with the bank managers. The interviews were then supplemented with data collected from secondary sources, such as brochures and articles. The study begins with the essential background introducing the banking industry. This is followed by a brief account of the development of marketing in the consumer loans market of the banking industry. The body of the report consists of the marketing strategies of two local banks and a foreign bank. The study also analyses the differences among the three banks in pursuing the consumer loan market as well as how they address the issues pertinent to this market. A future outlook of the consumer loans market is presented in the conclusion.